Die liggaam-van-Christus-metafoor: bediening van die AGSlidmaat - Olwagen, JM; Putter, APJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2011)
Certain questions can be asked considering New Testament guidelines with regard to the functioning and expectations of an assembly structure surrounding the origin of the AFM church: Is the ministry of the AFM-pastor and member still relevant? Are the pastors successful in effectively guiding their assemblies in making use of their own members for voluntary acts of service? This entails the caring of their member and the execution of the assemblies’ missional command? How can the pastors systematize their ministries in such a way that the equipping task of members can be made more effective? This task implies the discovery and equipping of members for voluntary acts of service in the assembly as described amongst others in Ephesians 4:12. The purpose of this article is to provide a better understanding concerning the body-of-Christ-metaphor: ministry of an AFM assembly member.